Description Of the Nutritional Status of Young Women at SMP YPAK PTPN III SEI KARANG - Dea Febrina; Rani Suraya; Elsa Yoreina Purba; Jelita Suryani Siregar; Putri Suci Ramadiah; Sheila Megarani (KOLABORASI: Journal of Multidisciplinary, 2025)
Adolescent girls are a group that is vulnerable to nutritional problems. The nutritional status index for female adolescents aged 13–15 years in Medan City is 8,12% undernutrition and 22,29% overnutrition. This figure is higher than the nutritional status of North Sumatra, which is 7,3% undernourished and 17,7% overnourished. This study aims to determine the nutritional status of adolescent girls at YPAK PTPN III Sei Karang Middle School. This type of research is quantitative descriptive research with a cross-sectional study design, which means that data is collected simultaneously or all at once with a sample size of 50 people. The results showed that the BMI of 40 respondents (80%) had normal nutritional status, 6 people were undernourished (12%), 3 people were overnourished (6%), and 1 person was obese (2%). The upper arm circumference of respondents was normal (23,5–28,5 cm) 35 people (70%), malnourished (<23,5) 11 people (22%) and overnourished (>28,5 cm) 4 people (8%). From the results of this research, it can be concluded that the majority of adolescent girls have good nutritional status.